Świadkowie. Przy torze kolejowym Andrzeja Brzozowskiego - Preizner, Joanna (Postscriptum Polonistyczne, 2020)
The starting point is the explanation of how Zofia Nałkowska got the story idea for her most famous book Medallions while working on the Committee for Investigation of Nazi War Crimes in Poland. The author then proceeds to analyse Andrzej Brzozowski’s études. She focuses on “By the Railway Track” describing in detail the plot and the vicissitudes of the film before it was relased. The film holds a special place in Polish history as it was shelved in the archives for 28 years.